Investigation Produce of Particleboard with use of Bagasse and Haloxylon sp. in - Ali Khalili gasht (Regional Information Center for Science and Technology (RICeST), 2009)
In this study, for optimum using of agriculture residual and high density spices with a little consumption in the particleboard, the possibility of Haloxylon sp. use of the desert regions’ of Kerman and Bagasse available in the sugar came fields of Khuzestan province  was investigated. For this purpose of above mentioned raw materials with differente mixture percentage and with change effective agents in uniform particleboard such as particle moisture and press time, samples were made, and then were investigated mechanical and physical properties. For assessing the physical properties such as water absorption and mechanical properties such as rupture modulus, elasticity modulus and internal bonding were used according to the ASTM D-1037 standard. Results of this study showed that with increase amounts of Haloxylon sp. to 40%, rupture modulus and elasticity modulus increased and a great amount cause these strengths decreased. Also with increasing Haloxylon sp. amount to 60%, internal bonding values of boards increased and after this amount internal bonding decreased. With increased Haloxylon to 40%, water absorption in 2 & 24 hours decreased and then increased. Uniform particleboard rupture and elasticity modulus with increasing particle moisture to12% increased and then decreased. The Internal bonding with increasing moisture decreased. Optimum amount of moisture for absorption in 2 & 24 hours was 12%. The best press time for total strength in this study was 6 minutes